The origin of the Syriac apocryphal Psalm 153 - Van Rooy, H.F. (Unisa Press, 1994)
A survey is given of research on the Syriac apocryphal Psalm 153. As is the case with Psalm 152 a Hebrew Vorlage of this psalm does not form part of the Psalms Scroll from Qumran. That scroll does, however, contain Hebrew versions of Psalms 151, 154 and 155. The variants in the different Syriac manuscripts are discussed, demonstrating that all the variants can be regarded as the result of the inner Syriac transmission. The psalm is retroverted in Hebrew and the problems in this regard are discussed. This psalm is an individual lament. The possibility of the existence of a Hebrew Vorlage is discussed and it is concluded that such a Vorlage is a distinct possibility, with an origin for the psalm in the late Persian, early Hellenistic era.